Plasma and aqueous humor levels of adiponutrin and pannexin 1 in patients with and without diabetic retinopathy - Gul, Fatih Cem; Kobat, Sabiha Gungor; Celik, Fatih; Aydin, Suleyman; Akkoc, Ramazan Fazil (Ijo Press, 2022)
AIM: To evaluate plasma and aqueous levels of adiponutrin and pannexin 1 in patients with and without diabetic retinopathy. METHODS: The study included three age and gender-matched groups of 20 cataract patients with no diabetes or additional disease (Group C), 20 cataract patients with diabetes and no retinopathy (Group DM+C), and 20 cataract patients with diabetic retinopathy (Group DR+C). All the patients were examined with respect to body mass index (BMI), fasting plasma glucose, hemoglobin A1e (HbA1c), and lipid profile. Phacoemulsification and intraocular lens (Phaco+IOL) implantation were performed to all patients in all the groups, and aqueous samples were taken during the operation. The plasma and aqueous adiponutrin and pannexin 1 levels were analyzed using enzyme-linked immunosorbent assays. RESULTS: A statistically significant difference was determined between the groups with respect to BMI, fasting plasma glucose, and HbA1c levels (P<0.05 for all parameters tested). The plasma adiponutrin levels of Group DR+C were statistically significantly lower than those of Group C and Group DM+C (P<0.001, P=0.004). No statistically significant difference was determined in the aqueous adiponutrin levels in three groups. The plasma pannexin 1 levels of Groups DM+C and DR+C were statistically significantly lower than those of Group C (both P=0.001). The aqueous pannexin 1 levels of Group DR+C were statistically significantly higher than those of Group C and Group DM+C (P=0.001, P<0.001). CONCLUSION: Adiponutrin and pannexin 1, which play an important role in the pathophysiology of diabetes and obesity, and have a regulatory role in hyperglycemia and insulin resistance. The measurement of adiponutrin and pannexin 1 levels may support clinicians in determining the risk of DR development.
Keywords: diabetes mellitus; retinopathy; adiponutrin; pannexin 1